Pengembangan Media Pembelajaran Mengguankan Aplikasi Macromedia Flash pada Mater Teks Prosedur di Kelas IV Sekolah Dasar - Harahap, Nur Amiroh Ifada; Muhammadi, Muhammadi (Indo-MathEdu Intellectuals Journal, 2025)
The purpose of this research is to develop learning media using Macromedia Flash application on procedural text material in the fourth grade of elementary school that is valid, practical, and effective. The development of this learning media using the Macromedia Flash application employs a research development type in the form of (R&D) with the ADDIE model which has five stages, namely analysis, design, development, implementation, and evaluation. The data obtained are based on questionnaire responses from three validators, namely validation by subject matter experts, media experts, and language experts, as well as practicality questionnaires from teachers and students. The results of this study indicate that: (1) the overall validation results of the learning media by three validators, namely the material aspect, language aspect, and media aspect obtained an average percentage score of 94.08% with a very valid category, (2) the practicality test results of the learning media by teachers and students showed scores that were very practical with percentages at SDN 20 Indarung of 94.2% by teachers and 89% by students, while at SDN 13 Batu Gadang the percentage by teachers was 97.1% and 91.37% by students. The effectiveness of the media is proven through N-Gain Score analysis with a percentage of 69% which falls into the fairly effective category. Thus, it can be concluded that the learning media using Macromedia Flash applications on procedural text material in 4th grade elementary school has been declared valid, practical, and fairly effective for use in the learning process